Reflective Evaluation of Efl Teachers Versus Their Students’ Evalution - Wiwik Andreani (Lingua Cultura, 2010)
Article investigated the grading of teaching values and its relation to the rating performance of the teachers. For this purpose, 27 EFL teachers were randomly chosen from Bina Nusantara University. Some teachers taught only English Department students and some others taught students of other Departments, for example Computer Science, Marketing Communication, Management, Visual Communication Design and Chinese Department. They were asked to grade twelve values in their teaching according to the order of importance and to answer a set of questions on those values. Besides, their students filled in a questionnaire with the aim of evaluating the teachers’ performance from September 2008 until June 2010 (three semesters).The results of the study suggest that there is a change in the teaching-value grading along with teaching experience. However, there is no relationship between teaching values and getting high/low rating performance, the reason of which is not dealt with in the study. Expertise, Enthusiasm, Reliability and Attentiveness were teaching values selected as most important for the EFL teachers. Moreover, most teachers were graded higher in their soft skills rather than hard skills, especially in giving the students an opportunity to ask questions and to have a discussion during the teaching and learning process. Finally, when teachers taught small and big classes, surprisingly most of them got higher rating performance from their students of big classes, for both their hard and soft skills.